Implementation outcomes of a sensory integration therapy program with computerized dynamic posturography in patients with balance and sensory dysfunction - Gonzalez Eslait, Francisco Javier; Escudero Triviño, Paola Andrea; Giraldo Vergara, Yaidy Viviana; Morales García, Mónica Andrea; Lucero Gutiérrez, Vanessa Fernanda (Journal of otology, 2023)
We describe the first-year implementation experience of an Instrumented Sensory Integration Therapy Program in Audiological & Balance Center patients. This is a retrospective descriptive study. Participants included Seventy-three adults with diagnoses of acute, episodic, or chronic vestibular syndromes. They were classified into the following two groups: group 1 included 46 individuals treated with ISIT plus VRT, and group 2 included 27 individuals treated only with ISIT. The Sensory Organization Test (SOT) for both groups showed a statistical significance for all three sensory inputs; visual systems (G1: p = 0.0003; G2: p = 0.0337), vestibular system (G1: p < 0.0001; G2: p = 0.0003), and balance as demonstrated by compound balance score (G1: p < 0.0001; G2: p = 0.0035), and balance percentage deficit (G1: p < 0.0001; G2: p = 0.0078). The severity and complexity of functional neurological disorders in the context of vestibular syndromes seem to require between 10 and 20 therapy sessions, and combined ISIT plus VRT appears to be more effective than ISIT as a monotherapy.